BASIC CHARACTERISTICS OF LIVESTOCK INSURANCE IN SERBIA - WITH REFERENCE TO THE SOME ELEMENTS OF THIS TYPE OF INSURANCE IN SOME NON-EUROPEAN AND EUROPEAN COUNTRIES - Čolović, Vladimir; Petrović, Zdravko; Mrkšić, Dragan (Economics of Agriculture, 2016)
The livestock insurance is a part of agricultural insurance. This type of insurance is also part of a non-life insurance. The livestock insurance is undeveloped in Serbia. In general, a very small number of farms (5% of total) decided for the conclusion of livestock insurance contracts. This paper analyzes the basic characteristics of this type of insurance, and the authors pay attention to the implementation of this type of insurance in other countries. Special attention is paid to the livestock insurance in Mongolia, India, Mexico and Ireland who are defned livestock insurance programs that have contributed to a greater number of contracts concluded in this feld. Also, the authors speaking about livestock insurance in some European countries. Finally, the authors criticize the way in which is regulated livestock insurance in Serbia, by proposing a series of measures that should be implemented by the insurance companies and state.